Dominant contribution of Asgard archaea to eukaryogenesis - Victor Tobiasson; Jacob Luo; Yuri I. Wolf; Eugene V. Koonin (Nature, 2026)
Abstract The origin of eukaryotes is one of the key problems in evolutionary biology 1,2 . The demonstration that the last eukaryotic common ancestor (LECA) already contained the mitochondrion—an endosymbiotic organelle derived from an alphaproteobacterium—and the discovery of Asgard archaea—the closest archaeal relatives of eukaryotes 3–7 —inform and constrain evolutionary scenarios of eukaryogenesis 8 . We conducted a comprehensive analysis of the origins of core eukaryotic genes tracing to the LECA within a rigorous statistical framework centred around evolutionary hypothesis testing using constrained phylogenetic trees. The results show dominant contributions of Asgard archaea to the origin of most of the conserved eukaryotic functional systems and pathways. A limited contribution from Alphaproteobacteria was identified, relating primarily to energy transformation systems and Fe–S cluster biogenesis, whereas ancestry from other bacterial phyla was scattered across the eukaryotic functional landscape, without clear, consistent trends. These findings imply a model of eukaryogenesis in which key features of eukaryotic cell organization evolved in the Asgard lineage leading to the LECA, followed by the capture of the alphaproteobacterial endosymbiont and augmented by numerous but sporadic horizontal acquisitions of genes from other bacteria both before and after endosymbiosis.